Tuning the oxygen evolution reaction activity of Co3O4 nanocubes via controlled metal doping and surface faceting - Hatem M.A. Amin; Carsten Placke-Yan; Georg Bendt; Ulrich Hagemann; Stephan Schulz (Chemical Engineering Journal, 2026)

Contrasting release of redox-sensitive arsenic and uranium induced by heterotrophic denitrification in alluvial sediments - Kai Nils Nitzsche; Juan Carlos Richard-Cerda; Claudia Ullrich; Moritz Bigalke; Stephan Schulz (Environmental Pollution, 2026)

Grundwasserdaten: Zugänglichkeit, Anforderungen und Potenziale für Forschung, Praxis und Gesellschaft - Wiebke Warner; Christian Moeck; Ezra Haaf; Tanja Liesch; Pia Ebeling; Stefan Broda; Stephan Schulz (Grundwasser, 2025)

Eine Übersicht über die Auswirkungen des Klimawandels auf das Grundwasser in Deutschland und der Schweiz - Christian Moeck; Stephan Schulz (Grundwasser, 2025)
Zusammenfassung Der Artikel gibt einen Überblick über die Auswirkungen des Klimawandels auf Grundwasserressourcen in Deutschland und der Schweiz auf der Grundlage von Forschungsergebnissen von 2020 bis 2024. Die 12 ausgewählten Studien verdeutlichen die erheblichen Herausforderungen für Grundwassersysteme sowie deren nachhaltige Bewirtschaftung durch veränderte Niederschlagsmuster, steigende Temperaturen und extreme Wetterereignisse. Prognosen zeigen mögliche Rückgänge der Grundwasserstände in Nord- und Ostdeutschland sowie steigende Temperaturen in der Schweiz und Süddeutschland. Diese Veränderungen könnten gravierende Folgen für Ökosysteme und die Wasserversorgung haben. Die Vorhersagen unterliegen jedoch großen Unsicherheiten aufgrund der verschiedenen Klimaszenarien und aufgrund der Tatsache, dass die Modelle oft komplexe Zusammenhänge wie Landnutzungsänderungen und menschliche Eingriffe nur bedingt berücksichtigen. Trotz dieser Unsicherheiten betonen die Studien die Notwendigkeit nachhaltiger Managementstrategien. Weitere Forschung und verbesserte Grundwasser-Messnetze sind erforderlich, um die Unsicherheiten zu verringern und effektive Anpassungsstrategien zu entwickeln.

New insights on the formation of the polymetamorphic Felbertal tungsten deposit (Austria, Eastern Alps) revealed by CL, EPMA, and LA-ICP-MS investigation - Cordula P. Haupt; Joachim Krause; Bernhard Schulz; Jens Götze; Johannes Chischi; Jasper Berndt; Stephan Klemme; Steffen Schmidt; Karsten Aupers; Nils Reinhardt (Mineralium Deposita, 2025)
The Felbertal tungsten deposit is the only economic scheelite mine in Europe, yet its genesis is not fully understood. It has been argued recently that the formation of the deposit is most likely related to granitic intrusions of Variscan age, contrasting a previously suggested syn-depositional stratabound origin of Early Cambrian age. Solving this controversy remains challenging due to the polymetamorphic evolution of the deposit, which experienced both Variscan and Alpine metamorphism. In this contribution we present a comprehensive new data set of scheelite major, minor, and trace element concentrations from multiple scheelite generations of the Felbertal deposit along with microstructural observations. Our results show that Mo, Mo/Mn, REE, Y/Ho, Nb, and Nb/Ta in scheelite are variable within the different scheelite generations and are predominantly controlled by the host-rock lithologies on the local scale, whereas in general the data show a strong response to the shift of P, T, and pH upon changing magmatic-hydrothermal to metamorphic conditions. For the first time, we identify remnants of primary scheelite in the Western Ore Zone. The presented data support a magmatic-hydrothermal origin of the first scheelite mineralization during the Variscan orogeny with primary scheelite being characterized by wing-shaped REE patterns with a negative Eu-anomaly, high trace element concentrations, non-chondritic Y/Ho, and high Nb/Ta. Primary scheelite underwent metamorphic/hydrothermal alteration (recrystallization and dissolution-reprecipitation processes) during the Variscan and Alpine orogeny. This case study highlights that indicative mineralization-controlling geochemical ratios like Sr/Mn cannot be applied for polymetamorphic tungsten deposits like Felbertal.

The vulnerability of winter wheat in Germany to air temperature, precipitation or compound extremes is shaped by soil-climate zones - Rike Becker; Bernhard Schauberger; Ralf Merz; Stephan Schulz; Christoph Gornott (Agricultural and Forest Meteorology, 2025)

Infiltration of secondary treated wastewater into an oxic aquifer: Hydrochemical insights from a large-scale sand tank experiment - Marcel Horovitz; Edinsson Muñoz-Vega; Kay Knöller; Teresa E. Leitão; Christoph Schüth; Stephan Schulz (Water Research, 2024)

Assessing the impact of climate change on spring discharge using hydrological modelling in Musanze District, Rwanda - Joseph Muhumure; Eric Pohl; Stephan Schulz (Hydrogeology Journal, 2024)
Climate change has far-reaching impacts on water availability globally, with changing precipitation patterns and global warming contributing to increasing scarcity and unreliability of spring water in many regions. Despite this understanding, the implication of climate change on the hydrological system remains limited in certain areas, including the district of Musanze, Rwanda. This study investigates the effects of climate change on the discharge of 14 springs in Musanze using the hydrological model V2Karst. CORDEX data from two global climate models of CMIP5 are used to simulate the future spring discharges over the period 2021–2100. The results reveal significantly higher annual discharges in the RCP2.6 scenario compared to the RCP8.5 for all springs from 2021 to 2100. Nevertheless, no significant long-term trend in spring discharge is observed between the early (2021–2050) and late (2071–2100) periods. However, the intra-annual temporal discharge patterns are changing with a significant increase in the seasonality index for the RCP8.5 scenario towards the end of the twenty-first century. Additionally, for both RCPs, there is a notable increase in the number of days with discharges below 40% of the mean of annual discharges during the baseline period. The overall findings of this study suggest that climate change significantly impacts the future evolution of spring discharges in Musanze, indicating potential risks to the future availability of water in the region.

Correction to: The RESIST Senior Individuals Cohort: Design, participant characteristics and aims - Lennart Matthias Roesner; Manoj Kumar Gupta; Verena Kopfnagel; Nienke van Unen; Yvonne Kemmling; Jana‑Kristin Heise; Stephanie Castell; Xun Jiang; Lennart Riemann; Stephan Traidl; Berit Lange; Kurt‑Wolfram Sühs; et al. (GeroScience, 2024)

The RESIST Senior Individuals Cohort: Design, participant characteristics and aims - Lennart Matthias Roesner; Manoj Kumar Gupta; Verena Kopfnagel; Nienke van Unen; Yvonne Kemmling; Jana-Kristin Heise; Stephanie Castell; Xun Jiang; Lennart Riemann; Stephan Traidl; Berit Lange; Kurt-Wolfram Sühs; et al. (GeroScience, 2024)
The number of older adults worldwide is growing exponentially. However, while living longer, older individuals are more susceptible to both non-infectious and infectious diseases, at least in part due to alterations of the immune system. Here, we report on a prospective cohort study investigating the influence of age on immune responses and susceptibility to infection. The RESIST Senior Individuals (SI) cohort was established as a general population cohort with a focus on the elderly, enrolling an age- and sex-stratified sample of 650 individuals ( n = 100 20-39y, n = 550 61-94y, 2019–2023, Hannover, Germany). It includes clinical, demographic, and lifestyle data and also extensive biomaterial sampling. Initial insights indicate that the SI cohort exhibits characteristics of the aging immune system and the associated susceptibility to infection, thereby providing a suitable platform for the decoding of age-related alterations of the immune system and unraveling the molecular mechanisms underlying the impaired immune responsiveness in aging populations by exploring comprehensive, unbiased multi-omics datasets.

Competitive sorption experiments reveal new regression models to predict PhACs sorption on carbonaceous materials - Edinsson Muñoz-Vega; Marcel Horovitz; Lisa Dönges; Thomas Schiedek; Stephan Schulz; Christoph Schüth (Journal of Hazardous Materials, 2024)

LREE rich perovskite in antiskarn reactions - REE transfer from pyroxenites to carbonatites? - Daria Voropaeva; Andrei A. Arzamastsev; Roman Botcharnikov; Stephan Buhre; Sabine Gilbricht; Jens Götze; Reiner Klemd; Bernhard Schulz; Marion Tichomirowa (Lithos, 2024)

Preface: Hydrogeology of arid environments - Stephan Schulz; Viviana Re; Seifu Kebede; Osman Abdalla; Wenke Wang; Craig Simmons; Nils Michelsen (Hydrogeology Journal, 2024)

Do you consider dry deposition in your chloride mass balance to estimate groundwater recharge? Yes, no, maybe - Nils Michelsen; Matin Rezvani; Stephan Schulz (Hydrogeology Journal, 2024)
The popular chloride mass balance (CMB) method is often praised for its simplicity, especially in the groundwater recharge context. While some involved variables are indeed easy to obtain, the required atmospheric (wet/dry) chloride deposition is difficult to quantify. A literature survey, conducted for Africa and the Middle East, revealed surprising differences in the chosen approaches. This essay does not offer easy answers, but in view of many insufficiently described methodologies, it calls for more transparency in CMB studies.

Past and future impacts of land-use changes on ecosystem services in Austria - Uta Schirpke; Erich Tasser; Stefan Borsky; Martin Braun; Josef Eitzinger; Veronika Gaube; Michael Getzner; Stephan Glatzel; Thomas Gschwantner; Mathias Kirchner; Georg Leitinger; Bano Mehdi-Schulz; et al. (Journal of Environmental Management, 2023)

Age and petrogenesis of Ni-Cu-(PGE) sulfide-bearing gabbroic intrusions in the Lausitz Block, northern Bohemian Massif (Germany/Czech Republic) - Tom Járóka; Jörg A. Pfänder; Thomas Seifert; Folkmar Hauff; Blanka Sperner; Sebastian Staude; Tobias Stephan; Bernhard Schulz (Lithos, 2023)

Evaporation from the dried-up lake bed of Lake Urmia, Iran - Sahand Darehshouri; Nils Michelsen; Christoph Schüth; Massoud Tajrishy; Stephan Schulz (Science of The Total Environment, 2023)

Correction to: Self‑reported cardiovascular health of teachers: results from the 5‑year follow‑up of the Gutenberg Health Study cohort - Merle Riechmann‑Wolf; Sylvia Jankowiak; Andreas Schulz; Janice Hegewald; Karla Romero Starke; Falk Liebers; Karin Rossnagel; Alicia Poplawski; Natalie Arnold; Matthias Nübling; Andreas Seidler; Manfred Beutel; et al. (International Archives of Occupational and Environmental Health, 2021)

Self-reported cardiovascular health of teachers: results from the 5-year follow-up of the Gutenberg Health Study cohort - Merle Riechmann-Wolf; Sylvia Jankowiak; Andreas Schulz; Janice Hegewald; Karla Romero Starke; Falk Liebers; Karin Rossnagel; Alicia Poplawski; Natalie Arnold; Matthias Nübling; Andreas Seidler; Manfred Beutel; et al. (International Archives of Occupational and Environmental Health, 2021)
Objectives Following an exploratory approach, we examined cardiovascular disease risk factors at baseline and the 5-year incidence proportion of self-reported doctor-diagnosed cardiovascular diseases (CVD) in teachers and other occupational groups of the Gutenberg Health Study. Methods Study participants lived in the region of Mainz, Germany. Data from 6510 working participants without prevalent CVD at baseline (2007–2012) were analyzed. Participants were teachers ( n = 215), other professionals from the health, social or educational (HSE) fields ( n = 1061) or worked outside the HSE fields ( n = 5234). For occupational comparisons, we estimated prevalence ratios (PR) for each CVD risk factor at baseline with robust Poisson regression analyses. We calculated crude CVD incidence rates based on the observed 5-year CVD cumulative incidence at follow-up and estimated age-weighted incidence proportions. All analyses were stratified by sex. Results Male non-HSE workers showed a higher prevalence of smoking and physical inactivity than male teachers (PR 2.26; 95%-CI: 1.06–4.82/PR 1.89; 95%-CI: 1.24–2.87). In contrast, non-HSE workers and other HSE professionals were less likely to have reported an unhealthy alcohol intake than teachers. Differences were attenuated after SES-adjustment. We did not detect occupational group-specific differences in CVD incidence. However, there were only two cases of CVD among the teachers. Conclusion Particularly male teachers showed a healthier lifestyle regarding physical inactivity and smoking. Nevertheless, occupational-medical care practitioners and researchers need to be aware of the relatively heightened prevalence of unhealthy alcohol intake in female and male teachers, and in absolute terms, the high hypertension prevalence in male teachers.

Identifizierung der Eintragsquellen von Antibiotika in das Grundwasser viehstarker Regionen - Stephan Hannappel; Claudia Köpp; Sebastian Zühlke; Frederike Balzer; Dietrich Schulz (Grundwasser, 2016)

Die Bundeswasserstraßen als Energiespeicher — Potenzial und Herausforderungen - Thomas Weiß; Florian Grumm; Detlef Schulz; Stephan Mattner (WASSERWIRTSCHAFT, 2013)

The influence of the herbicide 2-methyl-4-chlorophenoxyacetic acid (MCPA) on the mineralization of litter-derived alkanes and the abundance of the alkane monooxygenase gene (alkB) in the detritusphere of Pisum sativum (L.) - Stephan Schulz; Tatiana Yuyunkina; Holger Pagel; Lukas Y. Wick; Christian Poll; Thilo Streck; Ellen Kandeler; Michael Schloter (Biology and Fertility of Soils, 2012)

Interacting effects of cation saturation and drying, freezing, or aging on the extractability of nonylphenol and phenanthrene from a sandy soil - Anastasia Shchegolikhina; Stephan Schulz; Bernd Marschner (Journal of Soils and Sediments, 2012)

Biosynthesis of (3Z,6Z,9Z)-3,6,9-Octadecatriene: The Main Component of the Pheromone Blend of Erannis bajaria - Stephan Goller; Gabor Szöcs; Wittko Francke; Stefan Schulz (Journal of Chemical Ecology, 2007)

Abstracts of the 6th FECS Conference 1998 Lectures - F. Sherwood Rowland; Donald R. Blake; B. R. Larsen; Anne Lindskog; Peter J. Peterson; W. Peter Williams; T. J. Wallington; M. J. Pilling; N. Carslaw; D. J. Creasey; D. E. Heard; P. Jacobs; et al. (Environmental Science and Pollution Research, 1998)